PENGARUH LINGKUNGAN KERJA DAN PENGHARGAAN TERHADAP PRESTASI KERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI ( Studi Pada Yayasan PAK Semarang ) - Priyadmadi, Yohanes Bagus; Basukianto, Basukianto (Jurnal Ilmiah Telaah Manajemen, 2015)
This study entitled Effect of Work Environment and Employee Appreciation Achievement Motivationas Mediating Variables in Semarang PAK Foundation . The problem of this study is how the role of the work environment , rewards and motivation on employee performance . This study aims to examine and analyze the role of work motivation in mediating the effect of the work environment and rewards on employee performance PAK Foundation Semarang . The population in this study are all employees of fixed and variable Foundation PAK Semarang . The study sample totaled 102 respondents were selected using purposive sampling method . Methods of data collection using questionnaires . The data analysis method used is regression analysis . Test mediation using path analysis path. The results of this study indicate that the work environment significantly influence motivation, reward significant effect on work motivation , work environment does not affect the performance , awards significant effect on job performance , motivation to work a significant effect on employees' work performance , work motivation mediates the effect of the work environment on employee performance and work motivation mediates the effect of rewards on employee performanceKeywords : work environment , respect, work motivation , employee job performance